Modern views on obesity and overweight in individuals after cholecystectomy as prerequisites for the substantiation and development of a physical rehabilitation program - Golod, Natalia (Journal of Education, Health and Sport, 2018)
Actuality. Cholelithiasis is one of the most common diseases of the gastrointestinal tract. The frequency of gallstones formation increases with age. The risk group includes women, individuals with diabetes mellitus, obese people, change their weight rapidly, as well as patients receiving hormone therapy or taking oral contraceptives. Objectives of research. To determine the prevalence of obesity and overweight in Ukraine. To analyze the impact of obesity and overweight in terms of the rehabilitation prognosis of patients after cholecystectomy. To identify the main means of physical rehabilitation to improve the quality of life of obese and overweight people. Results of research. Obesity affects 16% of the adult population of Ukraine. This is higher than the global average (8%). Losing weight too quickly can lead to certain problems: a decrease in muscle tissue, gallstones, nutritional deficiencies, etc. Losing a significant amount of weight in a short period of time often leads to weight gain again. Obesity has become a pandemic due to an obesogenic environment and an overemphasis on low fat intake, which leads to excessive consumption of simple carbohydrates and sugar. Conclusions. In individuals after cholecystectomy, overweight and obesity can lead to concomitant diseases of the cardiovascular, genitourinary, musculoskeletal systems, non-alcoholic fatty liver disease (NAFLD), type II diabetes mellitus, insulin resistance, cancer, depression, decreased social participation, decreased quality and life expectancy etc. The main means of physical rehabilitation to improve the quality of life of overweight and obese people after laparoscopic cholecystectomy (LCС) should be behavioral intervention strategies aimed at self-control, increased physical activity, diet, stress management (including sleep management). Even a 5-10% reduction in body weight has a significant positive impact on health. Physical activity (PA) should consist of multi-component exercises (aerobic and strength exercises, in middle age, elderly and senile age – in addition to the above, also exercises to train flexibility, balance to prevent falls). The risk of metabolic diseases can be reduced with 150 to 250 minutes of physical activity per week. A diet with an energy deficit of no more than 500 kcal and sufficient intake of high biological quality protein, along with calcium and vitamin D, complex carbohydrates and fiber. Physical rehabilitation programs should last at least 12 weeks.